Dialogue semiotics : theoretical groundwork for re-designing the syllabus in French as a foreign language for UiTM bachelor-candidates / Patrick Tourchon - Patrick, Tourchon (Universiti Teknologi MARA, Sarawak, 2003)
The methods for teaching French as a Foreign language are quite numerous, using books, audiocassettes, videos, CDs and CD-Roms. Moreover, since 1971, they all have been learner-centered, communication-based and interactive-wise. In this context, it is not clear why UiTM should need an in-house method for its Bachelor-candidate students.